Voices of young children aged 3–7 years in educational research: an international systematic literature review. Issue 1 (2nd January 2022) - Urbina-Garcia, Angel; Jindal-Snape, Divya; Lindsay, Angela; Boath, Lauren; Hannah, Elizabeth F. S.; Barrable, Alexia; Touloumakos, Anna K.
ABSTRACT: Although the importance of listening to young children's voices is acknowledged in international literature, it is not clear whether educational researchers really listen to them and, if they do, what research designs and methods facilitate that. Therefore, using the EPPI-centre approach (2007), a systematic literature review was undertaken of all papers published between 2015 and 2020 that indicated the author/s had listened to young children's (3–7 year-old) voices. The aim was to identify, appraise and synthesise international research focused on listening to their voices, and the research designs, methods of data collection and theoretical frameworks authors have used to achieve this. From the 74 studies that met the inclusion criteria, we found that there was some evidence of listening to young children's voices. However, there was a tendency to use adult-led methods rather than child-led methods along with the use of adult data sources for confirmation. Further, in many studies no specific theoretical framework was used. Based on our review of reviews, it is evident that this is the first international systematic review of its kind and provides unique insights that are relevant to researchers, professionals and policy makers internationally.